Block Practice Vs Random Practice: Bagaimana perbedaannya terhadap peningkatan gerakan senam forward roll? - Daharis; Rahmadani, Ahmad; Makorohim, M Fransazeli; Putra, Gilang Nanda (Edu Sportivo: Indonesian Journal of Physical Education, 2021)
This study aims to determine the difference in the effect of the block practice method and random practice on the improvement of the forward roll exercise. The method used is a quasi-experimental. The sample was divided into 2 groups, each of which consisted of 10 students in block practice and random practice groups. The research instrument uses a forward roll test which consists of three stages: the initial phase, the main phase, and the final phase. The data analysis technique used t test for different sample groups. Based on the results of the study, there were differences in the effect of block practice and random practice methods on the learning outcomes of forward roll gymnastics for students of Physical Education, Health and Recreation, Universitas Islam Riau. The results of data analysis also prove that there are differences in the average value of the two sample groups. In the sample group using the random practice method, the average value is 7.1, which is greater than the sample group using the block practice method with an average value of 7.9. That means that based on the results of the research, it turns out that the random practice method is superior to the block practice method in improving the forward roll exercise for students of Physical Education, Health and Recreation, Universitas Islam Riau.